An Effective Strategy to Construct Highly Efficient Deep‐Blue Organic Light‐Emitting Field‐Effect Transistors. Issue 17 (10th July 2017) - Tang, Guoqiang; Li, Bijin; Lan, Jingbo; You, Jingsong
Abstract : The fabrication of highly efficient deep‐blue organic light‐emitting field‐effect transistors (OLEFETs) remains a challenge due to the large energy bandgap of deep‐blue emitters. In this work, an effective strategy is developed by combining an ambipolar charge transport material with an efficient deep‐blue fluorescent emitter that features the hybridized local and charge‐transfer (HLCT) excited state character in a trilayer device architecture. The ambipolar nature of charge transport material endows the device with a relatively high hole–electron recombination efficiency, while the HLCT excited state character of the emitter offers the device a high singlet exciton yield. The device exhibits a maximum brightness of 710 cd m −2 and a maximum external quantum efficiency (EQE) of 0.28%, which is the first example of deep‐blue OLEFETs. Unlike conventional OLEFETs, the devices presented herein display high EQEs during almost the entire illumination. The EQE of device at the maximum brightness reaches 0.20%, which is the highest value among the reported blue OLEFETs. Moreover, the device exhibits an excellent color purity with a sharp emission peak at 445 nm, a narrow full‐width at half‐maximum of 58 nm, and a Commission Internationale de l'Eclairage coordinates of (0.15, 0.06) that is very close to the National Television System Committee standard blue (0.14, 0.08). Abstract : An effective strategy to construct highly efficient deep‐blue organic light‐emitting field‐effect transistors (OLEFETs) is developed by utilizing an ambipolar charge transport material and a deep‐blue emitter with hybridized local and charge‐transfer excited state character. The device displays a maximum brightness of 710 cd m –2 and a maximum external quantum efficiency of 0.28% with Commission Internationale de l'Eclairage coordinates of (0.15, 0.06), which is the first example of deep‐blue OLEFETs.